Immune checkpoint analysis in lip cancer. Issue 10 (October 2021) - Klein, M.; Wermker, K.; Hallermann, C.; Pannier, F.; Hölzle, F.; Modabber, A.
Abstract: The aim of this study was to establish whether PD-L1, PD-1, and markers of the tumor microenvironment (CD4, CD8, FOXP3) could have a prognostic value in squamous cell carcinoma of the lip (LSCC). In patients with histologically proven LSCC, tumor specimens were stained using immunohistochemistry (for PD-1, PD-L1, CD4, CD8, and FOXP3) on paraffin-embedded tissues. Patients with (N+) and without (N−) nodal metastasis were stratified and matched to each other according to prognostically relevant clinicopathological parameters. 58 patients (29 N+ and 29 N−) were included. PD-L1 expression was positive (>1%) in 56.1% (n = 33) of all LSCC cases, but its expression did not differ significantly between metastasis groups (65.5% in N+ versus 48.3% in N−; p = 0.144). Nodal disseminated LSCC showed a tendency for higher PD-L1 expression. None of the analyzed markers showed significant correlation with the risk for nodal disease, or revealed significant prognostic value. Due to their significant expression, PD-L1 and PD-1 are potential targets for checkpoint inhibitor therapy in LSCC. Their expression should be analyzed in advanced and metastasized LSCC cases.